Intelligent compaction technology for geomaterials. A demonstration project - Correia, A. Gomes (2014)
Intelligent Compaction (IC), which is a part of Compaction Management, is a real time automatic adjustment and continuous compaction control technology of geomaterials or asphalt layers. The adjustment of the compaction parameters by the equipment is conducted simultaneously to the compaction process, as well as the continuous measurement of a dynamic compaction value, which is an indicator of the material’s degree of compaction. This study seeks to assess the advantages and disadvantages of IC, as well as formulating a comparison with conventional compaction methods in terms of efficiency. This goal was achieved through in situ application of various technologies to two distinct types of material: a soil-rockfill mixture and a sandy soil. Data was obtained and analysed by the IC continuous information, as well as by the application of several different conventional compaction control tests and methods. Results show that the IC technology presents a superior performance, as well as various advantages when compared to conventional compactors.